EFEKTIVITAS EKSTRAK ETHANOL DAUN SALAM (SYZYGIUM POLYANTHUM) SEBAGAI LARVASIDA TERHADAP LARVA NYAMUK AEDES AEGYPTI - Ni Made Pasmiati Setyaningsih; I Kadek Swastika (Universitas Udayana, 2016)
THE EFFECTIVENESS OF SALAM LEAF ETHANOL EXTRACT (SYZYGIUM POLYANTHUM) AS LARVICIDE FOR AEDES AEGYPTI LARVAEThe cases number of dengue fever is high and fluctuating every year, signifying vector control program not yet optimal.An alternative that can be used that is using insecticide from plants. One of potentially as larvicide is salam leaf. The purpose of thisresearch was to know the effectiveness of salamleafextract(Syzigium polyanthum) in kills the Aedes aegypti larvae and LC50 and LC90 scores for observation 24 hours.This study is an experimental research with posttest only control design.The dosages of extracts tested were 0%; 2%; 4%; 6%; 8%; dan 10% with five times replication.The results showed there were no larval mortality in control group (0%). The percentage of larvae mortalitywere 32.8 %; 69.6 %; 74.4 %; 85.6 %; 94.4 % respectively at concentrations 2%; 4%; 6%; 8%; and 10%. The analysis of One Way Annova obtained p<0.05 means there were significance difference between the mortality ofAedes aegypti larvae with salamleaf extract given. The analysis of Probit obtainedLC50= 3.877% and LC90= 8.016%.It can be concluded that salamleaf ethanol extracts (Syzygium polyanthum) is effective in kills the Aedes aegypti larvae and there are connection between an increase in the concentration extract by the number of larvae mortality.